KEPASTIAN HUKUM PEROLEHAN HAK GUNA USAHA (HGU) PERKEBUNAN KELAPA SAWIT DALAM UPAYA MENCIPTAKAN IKLIM INVESTASI YANG KONDUSIF DI KABUPATEN PASAMAN BARAT (Studi Kasus PT. Laras Inter Nusa di Kabupaten Pasaman Barat) - Erlis Erlis (UNES Journal of Swara Justisia, 2018)
Indonesia, which is rich in natural resources and minerals, has the potential to develop the palm oil sector as one of the drivers of the nation's economic growth. But Indonesia is also not free from various deficiencies, unable to meet their own needs both in terms of physical and non physical as well as the needs of both consumptive and non consumptive. For example the procurement of advanced technology to cultivate a variety of natural wealth owned. So a necessity for Indonesia to build investments in the field of palm oil by attracting other countries into Indonesia to invest in managing minerals contained in the earth of Indonesia. Indonesia is required to move quickly with increasingly complex population stability, one of the causes is rampant unemployment. Based on the results of the discussion and analysis it can be concluded that the legal certainty of acquisition of HGU for investment activity for investors in the field of oil palm plantation in Pasaman Barat Regency is to run the business of investors who will do business in the field of oil palm plantation must first obtain a business license in the field of plantation from the Regent . This letter as to obtain a business location permit and environmental analysis certificate from the chairman Amdal letters are guaranteed legal certainty. Legal protection of Investor Protection against the acquisition of HGU for investment in palm oil plantation when land claims by the local community against land use in Indonesia are implemented in the Basic Agrarian Law and Investment Law. In both laws there is no discrimination of land rights granted by the Indonesian government.